Random amplified polymorphic DNA typing of Pseudomonas aeruginosa isolates recovered from patients with cystic fibrosis. - Mahenthiralingam, E (1996)
Pseudomonas aeruginosa isolates recovered from chronically colonized patients with cystic fibrosis (CF) are phenotypically different from those collected from other patients or from the environment. To assess whether alterations in motility, mucoidy, and serum susceptibility represented an adaptation to chronic infection or replacement by a new strain, sequential P. aeruginosa isolates of known phenotype collected from 20 CF patients were typed by random amplified polymorphic DNA (RAPD) analysis. A total of 35 RAPD strain types were found among 385 isolates from 20 patients, and only two patients had P. aeruginosa strains of the same RAPD fingerprint. Eight strain pairs representative of the first eight RAPD types were also analyzed by SpeI macrorestriction followed by pulsed-field gel electrophoresis (PFGE); the strain types found by both fingerprinting techniques correlated exactly. In 11 of 20 patients, the RAPD types of serial P. aeruginosa isolates remained stable despite alterations in isolate motility, colonial morphology, and lipopolysaccharide phenotype. However, in isolates collected from one CF patient, a single band change in RAPD fingerprint and CeuI PFGE profile correlated with the appearance of an RpoN mutant phenotype, suggesting that the altered phenotype may have been due to a stable genomic rearrangement. Secretion of mucoid exopolysaccharide, loss of expression of RpoN-dependent surface factors, and acquisition of a serum-susceptible phenotype in P. aeruginosa appear to evolve during chronic colonization in CF patients from specific adaptation to infection rather than from acquisition of new bacterial strains.